Sports genomics: Current state of knowledge and future directions - Ahmetov, I. I.; Fedotovskaya, O. N. (Cellular and Molecular Exercise Physiology, 2012)
Athletic performance is a heritable trait influenced by both environmental and genetic factors. Sports genomics is a relatively new scientific discipline focusing on the organization and functioning of the genome of elite athletes. With genotyping becoming widely available, a large number of genetic case-control studies evaluating candidate gene variants have been published with largely unconfirmed associations with elite athlete status. This review summarizes the evidence and mechanistic insights on the associations between DNA polymorphisms and athletic performance. A literature search (period: 1997-2012; number of articles: 133) revealed that at least 79 genetic markers are linked to elite athlete status (59 endurance-related genetic markers and 20 power/strength-related genetic markers). Importantly, we have identified 20 genetic markers (25.3%) that have shown positive associations with athlete status in at least two studies (14 endurance-related genetic markers: ACE I, ACTN3 577X, ADRB2 16Arg, AMPD1 Gln12, BDKRB2 -9, COL5A1 rs12722 T, GABPB1 rs7181866 G and rs12594956 A, HFE 63Asp, KCNJ11 Glu23, PPARA rs4253778 G, PPARD rs2016520 C, PPARGC1A Gly482, UCP3 rs1800849 T; and 6 power/strength-related genetic markers: ACE D, ACTN3 Arg577, AMPD1 Gln12, HIF1A 582Ser, NOS3 rs2070744 T, PPARA rs4253778 C). However, sports genomics is still in the discovery phase and abundant replication studies are needed before these largely pioneering findings can be extended to practice in sport. Future research including genome-wide association studies, whole-genome sequencing, epigenetic, transcriptomic and proteomic profiling will allow a better understanding of genetic make-up and molecular physiology of elite athletes.